2013
DOI: 10.1177/0954406213486592
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigation on the influence of main motor rotational frequency in fine-cropping

Abstract: The bar fine-cropping, the first and one of the most important metal-forming procedure, separates the work-piece into accurate products and billets. The aim of this article is to investigate the influence of different main motor rotational frequencies on a new fine-cropping system. Five different rotational frequencies are applied to both the numerical simulations and the fine-cropping experiments. The numerical and experimental results show that good agreement is achieved by combining the average stress triax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Zhao et al 8 pointed out that the metal bar’s stable crack propagation and fracture are obtained when constantly increasing the striking displacement and reducing the striking frequency in the cropping process, simultaneously. Tang et al 9,10 , Zhong et al 11 and Zhang et al 1 found that a linear increment of the stroke-time curve and a linear decrement of the strike frequency-time curve improve the cropping efficiency and the quality of the fracture section. By changing the above factors, the sufficient efficiency of cropping and qualified quality of cross-section get together.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al 8 pointed out that the metal bar’s stable crack propagation and fracture are obtained when constantly increasing the striking displacement and reducing the striking frequency in the cropping process, simultaneously. Tang et al 9,10 , Zhong et al 11 and Zhang et al 1 found that a linear increment of the stroke-time curve and a linear decrement of the strike frequency-time curve improve the cropping efficiency and the quality of the fracture section. By changing the above factors, the sufficient efficiency of cropping and qualified quality of cross-section get together.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still collapse zones left at the contact area of bars, together with serious problems as wear and breakage of the blade. Low stress blanking method, based on the crack technology, firstly cut annular grooves on the surface of the bars to generate stress concentration, and then apply circumferential cyclic load to accelerate the initiation and extension of fatigue crack [3,4], which can obtain billets with high quality section. Whereas, the blanking efficiency is relatively low(6~8 billets per minute); on the other hand, the stress grooves with V shape profiles [5] are mainly processed by lathe or milling, which don't generate severe stress concentration, and grooving of hard materials is still difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Some new different lowstress bar fine-cropping methods have been proposed based on the stress concentration in the last two decades. 4,[12][13][14][15][16] Although some of the disadvantages have been improved in some extent, the cross-section quality and the efficiency are still required to be improved indeed. Besides, due to lack of the correct and appropriate cropping mechanism, the optimal cropping load control strategy of the existing low-stress fine-cropping methods still remains unclear.…”
Section: Introductionmentioning
confidence: 99%